PENGEMBANGAN MODEL MANAJEMEN KURIKULUM PENDIDIKAN DAN IMPLEMENTASINYA PADA PELATIHAN DASAR KEMILITERAN KOMPONEN CADANGAN - Ansori Zaini; I Wayan Warka (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Curriculum management is a fundamental element in ensuring the effectiveness and sustainability of educational programs, including strategic education related to national defense and state resilience. Basic Military Training for the Reserve Component, as part of the Total Defense System, requires curriculum management that is not solely oriented toward military operational needs but is also aligned with systematic, adaptive, and sustainable educational curriculum management principles. However, studies that specifically develop a general model of educational curriculum management and examine its implementation in the context of Reserve Component training remain limited. This study aims to develop an educational curriculum management model and analyze its implementation in the Basic Military Training of the Reserve Component in Indonesia. This study employs a qualitative approach with a normative–empirical research design. Normative data were obtained through an analysis of the Regulation of the Minister of Defense of the Republic of Indonesia Number 4 of 2021 concerning the Curriculum for Basic Military Training of the Reserve Component. Empirical data were collected through in-depth interviews with the Head of the Reserve Component Division at the Ministry of Defense of the Republic of Indonesia. Data analysis was conducted using thematic analysis, encompassing the stages of curriculum planning, organizing, implementation, and evaluation as the core framework of educational curriculum management. The findings indicate that the curriculum management of the Basic Military Training for the Reserve Component has been systematically structured by integrating character and attitude development, knowledge and skills enhancement, and military physical training. Nevertheless, the implementation of the curriculum faces several challenges, particularly related to curriculum adaptability to the dynamics of modern defense threats, limitations in training resources, and the absence of a continuous curriculum renewal mechanism. Based on these findings, this study proposes a conceptual and applicative model of educational curriculum management that can be implemented in Reserve Component training and is also relevant for the development of other forms of strategic education. This model is expected to contribute to strengthening curriculum governance in state defense education. ABSTRAK Manajemen kurikulum merupakan aspek fundamental dalam penyelenggaraan pendidikan, termasuk pada pendidikan strategis yang berorientasi pada bela negara dan pertahanan. Pelatihan Dasar Kemiliteran Komponen Cadangan sebagai bagian dari Sistem Pertahanan Semesta membutuhkan pengelolaan kurikulum yang tidak hanya berfokus pada pemenuhan kebutuhan kemiliteran, tetapi juga selaras dengan prinsip-prinsip manajemen kurikulum pendidikan yang sistematis, adaptif, dan berkelanjutan. Namun, kajian yang mengembangkan model manajemen kurikulum pendidikan dan mengimplementasikannya secara komprehensif pada pelatihan Komponen Cadangan masih terbatas. Penelitian ini bertujuan untuk mengembangkan model manajemen kurikulum pendidikan serta menganalisis implementasinya pada Pelatihan Dasar Kemiliteran Komponen Cadangan di Indonesia. Penelitian ini menggunakan pendekatan kualitatif dengan desain normatif–empiris. Data normatif diperoleh melalui analisis Peraturan Menteri Pertahanan Republik Indonesia Nomor 4 Tahun 2021 tentang Kurikulum Pelatihan Dasar Kemiliteran Komponen Cadangan, sedangkan data empiris dikumpulkan melalui wawancara mendalam dengan Kepala Bagian Komponen Cadangan Kementerian Pertahanan Republik Indonesia. Analisis data dilakukan menggunakan analisis tematik yang mencakup tahap perencanaan, pengorganisasian, pelaksanaan, dan evaluasi kurikulum sebagai kerangka utama manajemen kurikulum pendidikan. Hasil penelitian menunjukkan bahwa manajemen kurikulum Pelatihan Dasar Kemiliteran Komponen Cadangan telah disusun secara terstruktur dengan mengintegrasikan pembinaan sikap dan perilaku, pengembangan pengetahuan dan keterampilan, serta pembinaan jasmani militer. Meskipun demikian, implementasi kurikulum masih menghadapi tantangan, terutama terkait dengan adaptasi kurikulum terhadap dinamika ancaman pertahanan modern, keterbatasan sumber daya pelatihan, serta mekanisme pembaruan kurikulum yang berkelanjutan. Berdasarkan temuan tersebut, penelitian ini menghasilkan model manajemen kurikulum pendidikan yang bersifat konseptual dan aplikatif, yang dapat diimplementasikan pada Pelatihan Dasar Kemiliteran Komponen Cadangan serta relevan bagi pengembangan kurikulum pendidikan strategis lainnya.